Endobiliary radiofrequency ablation combined with bilateral metal stent placement for malignant hilar biliary obstruction - Inoue, Tadahisa; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ohashi, Tomohiko; Nakade, Yukiomi; Sumida, Yoshio; Ito, Kiyoaki; Yoneda, Masashi (Endoscopy, 2020)
Background The effectiveness of endobiliary radiofrequency ablation (RFA) is still uncertain, especially in patients with malignant hilar biliary obstruction (MHBO). We examined the efficacy of endobiliary RFA followed by bilateral self-expandable metal stent (SEMS) placement for unresectable MHBO.Methods 41 patients met the eligibility criteria for study inclusion. We evaluated the technical success, functional success, and recurrent biliary obstruction (RBO) associated with RFA with bilateral SEMS placement.Results The technical and functional success rates were both 95.1 % (39/41). The RBO rate was 38.5 % (15/39), and the median time to RBO was 230 days. Stricture length was positively correlated with time to RBO in the multivariate analysis (P = 0.03). The median time to RBO was significantly longer in patients with strictures > 15 mm in length than in those with strictures ≤ 15 mm (314 vs. 156 days; P = 0.02).Conclusions The present study showed that endobiliary RFA with bilateral SEMS placement achieved good results, but selection of patients with an appropriate stricture length may be needed to obtain a sufficient ablative effect.